Animals, environment and sustainability: Global warming reducing and inducing attributes of the farm animals - SINGH, VIR; RASTOGI, AKANKSHA (The Indian Journal of Animal Sciences, 2021)
Animals, environment and sustainability are related with each other. The intricate soil-plant-animal relationship is vital for the very ecological integrity of the biosphere. Animal diversity, both inter- and intra-species, has multiple socio-economic attributes. In an agroecosystem with uncultivated land, cultivated land, livestock and households as the integral components, livestock play crucial role in transferring nutrients from ecologically more sustainable ecosystem (forest/ rangeland/ grassland) to ecologically vulnerable one (cultivated land), and in the recycling of nutrients in the cultivated lands. Draught animal power (DAP) is a key source for realizing sustainability in traditional agricultural systems which is ensured by their role in enhancing ecological processes—cropping diversification, agro-biodiversity maintenance, and soil fertility management. Farm animals also play negative role leading to environmental degradation through overgrazing and carbon emissions. Grazing animals significantly affect an ecosystem in triple ways, viz. herbivory, physical effects, and deposition. Overgrazing alters community structure as well as ecosystem functioning, including primary productivity and it has triggering effects on an ecosystem. Farm animals are key agents as well as sufferers of the on-going climate change. Their role in land degradation, water pollution, biodiversity erosion and release of GHGs contributes to exacerbate global warming.